2019
DOI: 10.1016/j.jmii.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study on clinical characteristics of Acinetobacter bacteremia in patients with liver cirrhosis

Abstract: Even though cirrhotic patients with Acinetobacter bacteremia were younger and had lower APACHE II scores than non-cirrhotic patients, the mortality rates were insignificantly different between the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Herein, we found that 77.78% of A. baumannii isolates were multidrug-resistant. Many studies have reported on the high rate of multidrug-resistant A. baumannii in hospital settings, especially among patients suffering from liver diseases [ 45 , 46 , 47 ]. This high rate of multidrug resistance needs prompt action to decrease the morbidity and mortality of the infections caused by these bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we found that 77.78% of A. baumannii isolates were multidrug-resistant. Many studies have reported on the high rate of multidrug-resistant A. baumannii in hospital settings, especially among patients suffering from liver diseases [ 45 , 46 , 47 ]. This high rate of multidrug resistance needs prompt action to decrease the morbidity and mortality of the infections caused by these bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Acinetobacter plays an important role in death caused by bacteremia in patients with liver cirrhosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Bacteraemia caused by the CR-Acb complex has been associated with a higher mortality rate and longer hospitalization compared to that caused by carbapenem-susceptible Acinetobacter strains [2]. A. baumannii and A. nosocomialis are commonly isolated clinical Acinetobacter species worldwide and account for more than 80 % of clinical infections caused by the CR-Acb complex in Taiwan [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…baumannii and A. nosocomialis are commonly isolated clinical Acinetobacter species worldwide and account for more than 80 % of clinical infections caused by the CR-Acb complex in Taiwan [3, 4].…”
Section: Introductionmentioning
confidence: 99%